EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER DENGAN PENDEKATAN SAINTIFIK DAN TIPE ROUNDTABLE DENGAN PENDEKATAN SAINTIFIK PADA MATERI FUNGSI DITINJAU DARI KECERDASAN EMOSIONAL SISWA KELAS VIII SMP NEGERI SE-KABUPATEN SUKOHARJO - Yolan Kusumaningtyas; Mardiyana Mardiyana; Budi Usodo (Universitas Sebelas Maret, 2015)
Abstract: The purpose of this study was to determine the effect of learning models on the learning achievement in Mathematics viewed from emotional intelligence of the students. The learning models compared were learning model of the Numbered Head Together (NHT) with scientific approach, Roundtable with scientific approach, and classical with scientific approach. The type of this study was a quasi-experimental study with a 3x3 factorial design. The population was all grade VIII students of Public Junior High Schools in Sukoharjo Regency. Instruments used for data collection were mathematics achievement test and emotional intelligence questionnaire. The data analysis technique used was the two-way ANOVA with unequal cell. Based on hypothesis, the results of the study concluded as follows. (1) Roundtable model with scientific approach got better learning achievement than NHT model with scientific approach and with classical model with scientific approach, NHT model with scientific approach got better learning achievement than classical model with scientific approach. (2) Students with high emotional intelligence gave the same learning achievement with the students who had middle emotional intelligence. In addition, students who had high and middle emotional intelligence have better learning achievement than students who had low emotional intelligence. (3) In each learning models, student with high emotional intelligence gave the same learning achievement with the students who had middle emotional intelligence, then students who had high and middle emotional intelligence have better learning achievement than students who had low emotional intelligence. (4) In each category of emotional intelligence, Roundtable model with scientific approach got better learning achievement than NHT with scientific approach and classical model with scientific approach, NHT model with scientific approach got better learning achievement than classical model with scientific approach.Keywords : Numbered Head Together (NHT), Roundtable, Classical, Scientific Approach, Emotional Intelligence.